Cyclotorsion measurement in laser refractive surgery - Lucena,Abrahão Rocha (2013)
PURPOSE: The aim of this study was to verify the presence of cyclotorsion in eyes that underwent laser refractive surgery. METHODS: This was a comparative observational study, which analyzed the medical records of 61 patients (104 eyes) who underwent laser refractive surgery and compared the axis of astigmatism of the sitting and the supine positions. Regarding the gender, 37.5% were male and 62.5% were female. The age ranged from 20 to 54 years old, with the median of 29 years. The lowest degree of astigmatism was -0.75 cylinder diopters (DC) and the highest was -6.50 DC, with a mean of -3.06 ± 1.16 DC. First, the axis of astigmatism of the seated patient was captured by the Schwind's ORK-CAM. In a second moment, inside the operating room, the axis of astigmatism of the patient in supine position was captured by the laser equipment's own camera (Schwind Amaris®), which was then compared with the previous measure. The incyclotorsion was defined by a minus sign (-) and the excyclotorsion, by a plus sign (+). RESULTS: The maximum excyclotorsion was +7.7 and the maximum incyclotorsion was -11.0 degrees. The mean torsion (excyclo or incyclo) was 2.74 (56.7%), with a standard deviation of 2.30 degrees. There was no statistically significant change (p=0.985) in the axis of astigmatism between patients sitting versus supine. CONCLUSION: There was clinically significant cyclotorsion in 36.5% of the eyes submitted to laser correction.